2018
DOI: 10.1016/j.bonr.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temporal onsets of mechanical loading on bone formation inside a tissue engineering scaffold combined with cell therapy

Abstract: Several approaches to combine bone substitutes with biomolecules, cells or mechanical loading have been explored as an alternative to the limitation and risk-related bone auto- and allo-grafts. In particular, human bone progenitor cells seeded in porous poly(L-lactic acid)/tricalcium phosphate scaffolds have shown promising results. Furthermore, the application of mechanical loading has long been known to be a key player in the regulation of bone architecture and mechanical properties. Several in vivo studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Research suggests that this process involves a link between inflammation and ectopic new bone formation: Activation of the canonical Wnt/β-catenin pathway and the non-canonical Wnt/PKCδ pathway is involved in inflammation-induced osteogenesis [22]. The process of osteoinduction is always accompanied by inflammation which was caused by surgical trauma, and the inflammation can activate endothelial cells and vascular endothelial growth factor (VEGF), etc., these cells and cytokines were usually used to be seed cells and osteogenic biomolecules in bone tissue engineering [23,24]. Our results show high levels of inflammation in the week following transplantation.…”
Section: Discussionmentioning
confidence: 56%
“…Research suggests that this process involves a link between inflammation and ectopic new bone formation: Activation of the canonical Wnt/β-catenin pathway and the non-canonical Wnt/PKCδ pathway is involved in inflammation-induced osteogenesis [22]. The process of osteoinduction is always accompanied by inflammation which was caused by surgical trauma, and the inflammation can activate endothelial cells and vascular endothelial growth factor (VEGF), etc., these cells and cytokines were usually used to be seed cells and osteogenic biomolecules in bone tissue engineering [23,24]. Our results show high levels of inflammation in the week following transplantation.…”
Section: Discussionmentioning
confidence: 56%
“…This aspect is more important in the case of bone healing, where multiple overlapping phases exist. Early loading from two days onwards has been reported less effective than delayed loading at two weeks 37 . However, it has also been reported that early cyclic loading may increase oxygen transport to the defect region 38 , promoting the longer term regeneration response.…”
Section: Discussionmentioning
confidence: 96%
“…As was previously demonstrated in human translational medicine, simultaneous isolation of various fetal progenitor cell types from one organ donation enable highly efficient research and therapeutic development in all major aspects of musculoskeletal cell therapies [45,53,56,59,60,63]. Such knowledge and experience were extrapolated to veterinary therapeutic research, as immune privilege of progenitor cells potentially allows for safe xenogeneic…”
Section: Fetal Progenitor Cell Sources For Regenerative Medicinementioning
confidence: 96%
“…Wound healing rates after progenitor cell applications have been shown to be relatively more important and prompt with little scar tissue formation and an absence of immunogenic or tumorigenic properties has been documented [43,[45][46][47][48]. Generalized and tissue-specific application of progenitor cell technology to musculoskeletal regenerative medicine has effectively been a local driver of translational biomedical research and is currently being evaluated for human and veterinary patients in Switzerland [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. The present work is consistent with the One Health Initiative (www.onehealthinitiative.com), an approach of integrative medicotherapeutic development under which veterinary medicine can benefit from human medicine and vice versa.…”
Section: Introductionmentioning
confidence: 99%